2017
DOI: 10.1002/glia.23284
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in CA1 hippocampal synapses in a mouse model of fragile X syndrome

Abstract: Fragile X Syndrome (FXS) is the major cause of inherited mental retardation and the leading genetic cause of Autism spectrum disorders. FXS is caused by mutations in the Fragile X Mental Retardation 1 (Fmr1) gene, which results in transcriptional silencing of Fragile X Mental Retardation Protein (FMRP). To elucidate cellular mechanisms involved in the pathogenesis of FXS, we compared dendritic spines in the hippocampal CA1 region of adult wild-type (WT) and Fmr1 knockout (Fmr1-KO) mice. Using diolistic labelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 82 publications
11
75
0
Order By: Relevance
“…The modification of dentate gyrus-hippocampal CA3 connections may affect the functional connectivity of the hippocampus with other brain regions, which is associated with autistic-like behaviors in mice (Zhan et al, 2014). In addition, the increased density of functional mossy fiber synapses in adult MIA offspring is consistent with previous studies that demonstrated increased excitability and spine density of hippocampal neurons in rodent models of ASD (Tyzio et al, 2014;Jawaid et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The modification of dentate gyrus-hippocampal CA3 connections may affect the functional connectivity of the hippocampus with other brain regions, which is associated with autistic-like behaviors in mice (Zhan et al, 2014). In addition, the increased density of functional mossy fiber synapses in adult MIA offspring is consistent with previous studies that demonstrated increased excitability and spine density of hippocampal neurons in rodent models of ASD (Tyzio et al, 2014;Jawaid et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…The frequency of neurodevelopmental disorders is positively correlated with maternal immune activation (MIA), which is induced by viral infection during pregnancy (Knuesel et al, 2014), and several studies have reported that deficits in synap-tic function and structure underlie the pathogenesis of neurodevelopmental disorders (Koyama and Ikegaya, 2015). Specifically, the disruption of synapse excitatory versus inhibitory (E/I) balance (Rubenstein and Merzenich, 2003;Yizhar et al, 2011;Tyzio et al, 2014) and the increased spine or synapse density (Tang et al, 2014;Jawaid et al, 2018;Andoh et al, 2016) are shared pathological features between ASD patients and ASD animal models. These findings motivated us to examine whether voluntary exercise in adulthood reverses the behavioral abnormalities and affects synaptic properties in mouse offspring prenatally subjected to MIA (MIA offspring).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with reported data in adult FMR1 knock-out mice suggesting cortical circuit changes such as increase in smaller size immature synapses and decrease in larger size synapses (as evidenced by the spine size in [35,71]), as well as decreased association of astrocytes with hippocampal synapses [35]. We have extended these observations, by showing that these changes are not uniform, but depend on the synapse type, as well as cortical layer.…”
Section: Discussionsupporting
confidence: 93%
“…The reduction in the mRNA of these molecules in this study would support that, at least at the gene level, alterations in the complement expression in the brain may result in synaptic hyperconnectivity as it has been shown in animals through reductions or knockout of pro-inflammatory cytokines [Chu et al, 2010;Weinhard et al, 2018]. Excessive hyperconnectivity of synapses has been shown in mouse models of syndromic ASD including fragile X, tuberous sclerosis, and 15q duplication [Jawaid et al, 2018;Sato & Okabe, 2019;Tang et al, 2014].…”
Section: Discussionsupporting
confidence: 79%